The Analysis of Students’ Vocabulary Mastery Who are using Tiktok Application - Lara Mauriza; Nurhafni Siregar (Medan Resource Center, 2022)
The aim of study is to examine the use of TikTok which is useful for improving students' vocabulary mastery. The research method used in this research is descriptive qualitative analysis method. This observation was carried out for 3 days starting on Sunday, April 10-13, 2022. The subjects of this study were selected into two groups, namely students who use TikTok and those who do not use TikTok, totaling 8 students as representatives of EFL students at UMN AL Washliyah Medan. Data collection techniques used were observation, interviews and tests, while data analysis used scoring techniques, then to find out the vocabulary mastery achieved by students, from all research data found 8 research subjects with 2 students actively watching review-based content with a vulnerable time where they often use their spare time to use this TikTok application. Students who were classified as active openly stated that the TikTok application really helped improve their vocabulary, to cover their difficulties in learning vocabulary. Meanwhile, students who do not use TikTok are divided into 1 student who relies on himself as a role in helping to learn vocabulary, 2 people rely on the people closest to them while 1 other student relies on a dictionary application in learning his vocabulary. This triggers them to not elaborate on the use of many applications, one of which is TikTok in covering their vocabulary learning difficulties. Some of the motivation they get in learning vocabulary is from the people closest to them such as parents, friends, teachers and even their smartphones help them improve their vocabulary, the only difference is parental control over them in using this application where active users get support use the application while those who are not users of the TikTok application do not. The results of this study show that students' vocabulary mastery is very influential on how active they are on social media, especially TikTok, it can be seen from the test scores of active users who do not use it and also parental control and their closest people are needed in the use of social media, especially TikTok. . Some of the other reasons people find it difficult to understand English is because they do not understand its meaning and rarely use it in their daily communication. Therefore, by increasing their vocabulary, it is easier for them to understand what they read, listen, write, and speak.